Analisis Economic Value Added (EVA) PT Mayora Indah Tbk Tahun 2020–2024: Evaluasi Kinerja Keuangan dan Arah Keberlanjutan - Masyhuri, Muhammad Ade (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to evaluate the financial performance of PT Mayora Indah Tbk through the Economic Value Added (EVA) method during the period 2020 to 2024. EVA is employed as an alternative metric to measure the extent to which the company creates value for its shareholders after accounting for the cost of capital. Using a quantitative-descriptive approach and secondary data from annual financial reports, the study finds that PT Mayora Indah Tbk consistently generated positive EVA values over the five-year period, indicating strong value creation. Moreover, the company's sustainability initiatives—such as emissions reduction and resource efficiency—support its long-term performance. These findings affirm the strategic alignment between financial management and sustainability practices.